Pemetaan Indeks Kesehatan Vegetasi di Kawasan Hutan DAS Terusan Batang - Rafi Riskullah Ahmad (JURNAL BUANA, 2022)
Forest area is a certain area that designated and determined by the government to maintain its existence as the permanent forest. The Terusan Batang watershed is located at the estuary of the Indragiri River which has various environmental problems such as inappropriate land conversion, coastal abrasion, and river pollution. The utilization of forest areas in the Terusan Batang watershed can be carried out optimally, if the health condition of vegetation in each forest area is in good condition. NDVI analysis is the standard method that used to compare greenery and vegetation health based on satellite imagery data. The study explains that although there are various environmental problems around the Terusan Batang Watershed, 99% of the total forest area in Terusan Batang Watershed still in a good-normal health condition of vegetation. It’s concludes that the Terusan Batang Watershed is still maintained so the utilization and function of the existing forest area can be carried out optimally.